2011
DOI: 10.1002/ebch.827
|View full text |Cite
|
Sign up to set email alerts
|

The prevention of eczema in infants and children: an overview of Cochrane and non‐Cochrane reviews

Abstract: Background Eczema is the most common inflammatory skin disease of childhood, characterized by an itchy red rash that usually involves the face and skin folds. There is currently no curative treatment for eczema, so the reduction of eczema incidence through disease prevention is a desirable goal. Potential interventions for preventing eczema include exclusive breastfeeding, hydrolysed protein formulas and soy formulas when bottle feeding, maternal antigen avoidance, omega oil supplementation, prebiotics and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 63 publications
1
60
0
1
Order By: Relevance
“…The first purpose is to present and describe the complete body of SR evidence on a clearly defined topic [26, 27]. The second purpose is to address a question that differs from the question(s) in the underlying SRs and that often relates to a subset of the questions in the SRs (e.g., subpopulations, or subsets of interventions or outcomes) [28, 29]. Distinguishing between these two purposes, and recognizing that different methods may be used for each, can help resolve some discrepancies and challenges likely to be encountered during the latter stages of the overview process.…”
Section: Discussionmentioning
confidence: 99%
“…The first purpose is to present and describe the complete body of SR evidence on a clearly defined topic [26, 27]. The second purpose is to address a question that differs from the question(s) in the underlying SRs and that often relates to a subset of the questions in the SRs (e.g., subpopulations, or subsets of interventions or outcomes) [28, 29]. Distinguishing between these two purposes, and recognizing that different methods may be used for each, can help resolve some discrepancies and challenges likely to be encountered during the latter stages of the overview process.…”
Section: Discussionmentioning
confidence: 99%
“…Data from studies done on large cohorts have not consistently shown a preventative effect of hydrolysed milk formulas on allergy and eczema development (36,37) but oligosaccharide-enriched formula was found to have an eczema preventive effect in children with low atopy risk in 3 studies (17,38,39).…”
Section: Accepted Articlementioning
confidence: 96%
“…Prevention of eczema has been covered in 40 systematic reviews 69 and one overview of the reviews 70 (see Chapter 1), which is itself a component of the eczema prevention work programme of this grant.…”
Section: Intravenous Immunoglobulin 186mentioning
confidence: 99%
“…Some other non-Cochrane reviews have been well reported and are mapped for further reference on the Centre of Evidence Based Dermatology resource section [see www.nottingham.ac.uk/dermatology (accessed 6 November 2015)]. Overviews of existing single intervention systematic reviews, such as the one conducted for eczema prevention, 70 are also needed, as is the application of mixed-treatment comparisons for understanding more about the crucial missing treatment comparisons that are needed to inform clinical practice.…”
Section: Secondary Researchmentioning
confidence: 99%